2014
DOI: 10.1002/2013gl058813
|View full text |Cite
|
Sign up to set email alerts
|

Cointrusive shear displacement by sill intrusion in a detachment: A numerical approach

Abstract: Sheared sills are observed at Piton des Neiges (the eroded basaltic volcano of La Réunion) and are a suspected cause of the coeruptive flank displacement of Piton de la Fournaise in 2007. We performed a 2-D numerical study to quantify the perturbation induced by sill injection within a volcanic edifice. Magma is considered as an inviscid and pressurized fluid injected in an initially stable edifice under gravity-controlled extension. Two cases of injection are tested, in an elastic homogeneous edifice or along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…On the other hand, events being located in a very limited depth range (±50 m around a east dipping plane), we cannot totally rule out the possibility that seismicity is triggered on a single slowly slipping plane. Such slow slip process has been observed on other volcanoes [ Cervelli et al , ; Segall et al , ] and might involve a subhorizontal detachment such as observed during the April 2007 Piton de la Fournaise eruption [ Got et al , ; Chaput et al , ; Froger et al , ]. To better understand the physical process driving the shallow seismicity, we are currently working on inferring focal mechanisms of shallow earthquakes.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, events being located in a very limited depth range (±50 m around a east dipping plane), we cannot totally rule out the possibility that seismicity is triggered on a single slowly slipping plane. Such slow slip process has been observed on other volcanoes [ Cervelli et al , ; Segall et al , ] and might involve a subhorizontal detachment such as observed during the April 2007 Piton de la Fournaise eruption [ Got et al , ; Chaput et al , ; Froger et al , ]. To better understand the physical process driving the shallow seismicity, we are currently working on inferring focal mechanisms of shallow earthquakes.…”
Section: Discussionsupporting
confidence: 89%
“…subvertical σ 3 ) would be attained by horizontal stress accumulation under the effect of recurrent dyke injections along the rift zones, and the subsequent permutations of the principal stress tensors, as evidenced for Piton des Neiges volcano, the inactive twin of Piton de la Fournaise. In such an evolution, sills act as detachment planes, restoring the extensional stress field (Famin and Michon, 2010;Chaput et al, 2014aChaput et al, , 2014b.…”
Section: Summit and Outer Rift Zones Related To The Shallow Plumbing mentioning
confidence: 99%
“…Field studies have highlighted the presence of sills and laccoliths in volcanic complexes [e.g., Pasquare and Tibaldi , ; Burchardt , ]. Numerous geodetic surveys have also revealed the emplacement of sills, some of which resulting in eruptions, among others, in the Galápagos Islands [e.g., Amelung et al , ], Eyjafjallajökull volcano, Iceland [e.g., Pedersen and Sigmundsson , , ; Sigmundsson et al , ], in the Afar region, Ethiopia [e.g., Nobile et al , ; Pagli et al , ], and Piton de la Fournaise volcano, Réunion Island [e.g., Chaput et al , ].…”
Section: Introductionmentioning
confidence: 99%